Black sun [large type] - Roanhorse, Rebecca (Roanhorse, Rebecca. Between earth and sky, 2021)
"In the holy city of Tova, the winter solstice is usually a time for celebration and renewal, but this year it coincides with a solar eclipse, a rare celestial event proscribed by the Sun Priest as an unbalancing of the world. Meanwhile, a ship launches from a distant city bound for Tova and is set to arrive on the solstice. The captain of the ship, Xiala, is a disgraced Teek whose song can calm the waters around her as easily as it can warp a man's mind. Her ship carries one passenger. Described as harmless, the passenger, Serapio, is a young man, blind, scarred, and cloaked in destiny. As Xiala well knows, when a man is described as harmless, he usually ends up being a villain.A god will return when the earth and sky converge under the black sun in the holy city of Tova."--